TAVI: 10 Years after the First Case - Rizzo, Toni (MD Conference Express, 2012)
The first human transcatheter aortic valve implantation (TAVI) was performed in 2002. Since then, TAVI has been evaluated as an alternative to surgical aortic valve replacement and medical treatment in several clinical trials. This article reviews the evidence from these trials. Also discussed are current tools for risk stratification and the risks of TAVI in low- and high-risk patients, and latest guidelines on the management of valvular heart disease.